225Actinium-labeled prostate-specific membrane antigen targeting peptide induces complete response in a metastatic prostate cancer patient. (May 2021) - Aras, Omer; Harmsen, Stefan; Ting, Richard; Sayman, Haluk B
Targeted radionuclide therapy has emerged as a promising and potentially curative strategy for high-grade prostate cancer. However, limited data are available on efficacy, quality of life, and pretherapeutic biomarkers. Here, we highlight the case of a patient with prostate-specific membrane antigen (PSMA)-positive metastatic castrate-resistant prostate cancer who displayed complete response to 225 Ac-PSMA-617 after having been resistant to standard-of-care therapy, then initially partially responsive but later resistant to subsequent immunotherapy, and resistant to successive 177 Lu-PSMA-617. In addition, the patient's baseline germline mutation likely predisposed him to more aggressive disease.